Perilaku Phubbing Sebagai Karakter Remaja Generasi Z - Youarti, Inta Elok; Hidayah, Nur (STKIP Muhammadiyah Pringsewu, 2018)
Preparing for the Z generation born and growing in the 21st century is clearly different from earlier generations. The various challenges of the times existed as though demanding renewal and acceleration in all aspects of life. Including one of them is in the field of communication technologies such as smartphones. The offer of modernity given also has a negative impact that is quite alarming. One of them is the emergence of the term phubbing as an indication of Z generation addiction to the smartphone makes a teenager willing to hurt the people around him with a nonchalant and more focused on the smartphone in his hand. Meanwhile, in terms of guidance and counselling, CBT approach is an appropriate therapy and can be used by a counsellor to overcome the phubbing behaviour. With the reduction of phubbing behaviour thanks to existing efforts, it is expected that teenagers social awareness can be further improved.Keywords: Generation Z, Phubbing, Cognitive Behaviour TeraphyÂ Â